2006
DOI: 10.1016/j.joca.2006.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Expression of superficial zone protein in mandibular condyle cartilage

Abstract: These results suggest that SZP plays an important role in boundary lubrication of mandible condylar cartilage, is synthesized locally within the condyle itself, and exhibits differential regulation by cell mediators relevant to mandibular condyle repairing and pathologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0
2

Year Published

2007
2007
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 36 publications
2
36
0
2
Order By: Relevance
“…This study provides new insight into the functional consequences of cytokine-mediated changes in lubricin metabolism reported previously (11,(27)(28)(29)(30)(31)(32). Changes in boundary mode eq (Figure 4) corresponded to previously demonstrated changes in lubricin localization induced by TGF␤1, IL-1␤, and OSM (27).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This study provides new insight into the functional consequences of cytokine-mediated changes in lubricin metabolism reported previously (11,(27)(28)(29)(30)(31)(32). Changes in boundary mode eq (Figure 4) corresponded to previously demonstrated changes in lubricin localization induced by TGF␤1, IL-1␤, and OSM (27).…”
Section: Discussionsupporting
confidence: 84%
“…Bovine cartilage explants exposed in vitro to transforming growth factor ␤1 (TGF␤1) demonstrate an up-regulation of lubricin synthesis and surface localization (11,(27)(28)(29)(30)(31). In addition, TGF␤1 is known to mediate lubricin expression, which colocalizes to areas of low friction coefficient within the joint (32), while insulin-like growth factor 1, another potent anabolic signaling molecule in cartilage, does not affect lubricin metabolism and localization (28).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Concentrations of TGF-b1 and IL-1b were chosen based on previous changes in SZP protein expression in culture. 19,20 A decrease in SZP protein expression has been observed for IL-1a treatment of articular cartilage 7,21,22 and for IL-1b in mandibular condyle chondrocytes 23 at similar concentrations.…”
Section: Tissue Acquisition and Culturementioning
confidence: 71%
“…Flannery et al (8) found that SZP accumulation by superficial zone chondrocytes from bovine articular cartilage was enhanced by TGF␤. Ohno and colleagues (27) reported that the expression and accumulation of SZP by fibroblasts derived from the fibrous zone of mandibular condyle cartilage was enhanced by TGF␤. In our laboratory, Khalafi et al (26) demonstrated that SZP accumulation was enhanced by BMP-7 in both explant cultures of superficial articular cartilage and monolayer cultures of superficial zone chondrocytes from bovine articular cartilage.…”
Section: Bmp Was Stronger Than That Of Superficial Zone Chondrocytesmentioning
confidence: 99%